Nivel de estrés y su relación con el desempeño laboral del profesional de enfermería en servicio de emergencia del hospital Carlos Lanfranco la Hoz Puente Piedra - 2021. - Ohashi Tuya, Hiroshi Christian (2022)
Objective: To analyze the relationship of the stress level with the work performance of the nursing professional in the Emergency Service of the Hospital Carlos Lanfranco La Hoz Puente Piedra - 2021. Material and method: This work is related to the quantitative approach, since the data collections, then hypotheses will be contrasted that will be supported by statistical analysis and analysis of the attributes or qualities that were described to find the results according to the behavior of the population. When talking about quantitative research, they are taken for granted to the statistical territory, which will base these approaches, because when analyzing the objective realities from making the numerical measurements, the predictions of the behavior of the problem or phenomenon will be made.